How to speak money : what the money people say-- and what it really means - Lanchester, John (W. W. Norton & Company, 2014)
Discusses how the world of finance and economics really works, from the terms and conditions of personal checking accounts to the deliberate concealments of bankers, and explains hundreds of common economic terms.